2017
DOI: 10.14740/jocmr3024w
|View full text |Cite
|
Sign up to set email alerts
|

In-Stent Restenosis due to Stent Recoil After Third-Generation Drug-Eluting Stent Implantation

Abstract: A 72-year-old man with a heavily calcified coronary lesion underwent percutaneous coronary intervention (PCI) using a third-generation drug-eluting stent (DES) with thin stent struts. Two months after the PCI, in-stent restenosis due to stent recoil (SR) occurred. An intravascular ultrasound (IVUS) revealed deformed stent struts and heavily calcified coronary plaque. The SR probably occurred due to persistent vessel compression as a result of heavily calcified coronary plaque. We should consider using a DES wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, it is unclear whether the occurrence of late‐acquired TP is correlated with restenosis and late stent thrombosis. Several recent reports have shown that the eccentric calcified protruding mass with an irregular surface confirmed by intracoronary imaging caused in‐stent restenosis early after DES implantation 22,23 . Therefore, it may be worthwhile to investigate with larger samples whether late‐acquired TP is associated with early and late in‐stent restenosis and thrombosis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, it is unclear whether the occurrence of late‐acquired TP is correlated with restenosis and late stent thrombosis. Several recent reports have shown that the eccentric calcified protruding mass with an irregular surface confirmed by intracoronary imaging caused in‐stent restenosis early after DES implantation 22,23 . Therefore, it may be worthwhile to investigate with larger samples whether late‐acquired TP is associated with early and late in‐stent restenosis and thrombosis.…”
Section: Discussionmentioning
confidence: 95%
“…Several recent reports have shown that the eccentric calcified protruding mass with an irregular surface confirmed by intracoronary imaging caused in-stent restenosis early after DES implantation. 22,23 Therefore, it may be worthwhile to investigate with larger samples whether lateacquired TP is associated with early and late in-stent restenosis and thrombosis. In any case, interventional cardiologists should be aware that late-acquired TPs might develop after DES implantation in lesions with calcified nodules and/or lipid-rich fibroatheroma.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in parallel with the reports from clinical observations of acute stent recoil by a heavily calcified plaque. [ 36 ] Interestingly, the performance of 0.07 mm AZ31 exceeded the 0.09 mm one in respect to the acute recoil. Indeed, before choosing the best option for stent, the status of the plaque should be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Of all 10 patients with IVUS catheter entrapment, 7 patients (70%) underwent placement of 3rd generation DES, which has thin stent struts and incorporates a durable and flexible structure [21]. Thin stent struts can minimize vascular injury and subsequent neointimal hyperplasia [22], and stent deliverability to a target lesion could be improved by reducing the stent strut thickness [23].…”
Section: Third-generation Desmentioning
confidence: 99%